Prognosis of hypoglycemia episode in cirrhotic patients during hospitalization - Hung, Tsung-Hsing; Tseng, Chih-Wei; Tsai, Chih-Chun; Lee, Hsing-Feng (BMC gastroenterology, 2021)
Background Studies have shown that hyperglycemia in cirrhotic patients increases mortality. However, no population-based study has evaluated the influence of hypoglycemia upon hospital admission on death in these patients. The aim of this study was to assess the effect of hypoglycemia at admission on the mortality of patients with liver cirrhosis. Methods The Taiwan National Health Insurance Database was searched, and 636 cirrhotic patients without baseline diabetes mellitus who presented with hypoglycemia upon hospitalized from 2010 to 2013 were included in the study. A one-to-four propensity score matching was performed to select a comparison group based on age, sex and comorbidities. Results The overall 30-day mortality rate was 30.2% in the hypoglycemia group and 7.4% in the non-hypoglycemia group (P < 0.001). After Cox regression modeling adjusting for age, sex and comorbid disorders, cirrhotic patients with hypoglycemia had a hazard ratio (HR) of 30-day mortality of 4.96 (95% confidence interval [CI] 4.05-6.08, P < 0.001) as compared to the non-hypoglycemia group. In subgroup analysis, the cirrhotic patients with hypoglycemia and hepatocellular carcinoma (HCC) had a 30-day mortality HR of 6.11 (95% confidence interval [CI] 4.40-8.49, P < 0.001) compared to those with neither hypoglycemia nor HCC. Conclusions Hypoglycemia is a very important prognostic factor in the 30-day mortality of cirrhotic patients, especially in those with underlying HCC. Keywords: Hypoglycemia, Cirrhosis, Mortality